2020
DOI: 10.1002/psp4.12492
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Data Assimilation to Support Informed Decision Making in Individualized Chemotherapy

Abstract: An essential component of therapeutic drug/biomarker monitoring (TDM) is to combine patient data with prior knowledge for model‐based predictions of therapy outcomes. Current Bayesian forecasting tools typically rely only on the most probable model parameters (maximum a posteriori (MAP) estimate). This MAP‐based approach, however, does neither necessarily predict the most probable outcome nor does it quantify the risks of treatment inefficacy or toxicity. Bayesian data assimilation (DA) methods overcome these … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 28 publications
0
54
0
Order By: Relevance
“…MAP estimation does not address the uncertainty of the posterior distribution and hence is not able to quantify the potential risk of the relevant clinical outcome. Recently, MAP-based approaches have been questioned in certain circumstances, such as when trough concentration is of interest because even a subtle discrepancy could be damaging for concentrations at a low level (18). Although a full Bayesian approach is superior to MAP-based approaches in handling mentioned issues, the benefit from such an approach could be limited or perhaps clinically irrelevant, due to the relatively large noise in the routine TDM data from ICU patients which influences the results as well.…”
Section: Discussionmentioning
confidence: 99%
“…MAP estimation does not address the uncertainty of the posterior distribution and hence is not able to quantify the potential risk of the relevant clinical outcome. Recently, MAP-based approaches have been questioned in certain circumstances, such as when trough concentration is of interest because even a subtle discrepancy could be damaging for concentrations at a low level (18). Although a full Bayesian approach is superior to MAP-based approaches in handling mentioned issues, the benefit from such an approach could be limited or perhaps clinically irrelevant, due to the relatively large noise in the routine TDM data from ICU patients which influences the results as well.…”
Section: Discussionmentioning
confidence: 99%
“…MIPD builds on prior knowledge from NLME analyses of clinical studies 21 . The structural and observational models are generally given as:dxdtt=fxt;θ,d,x0=x0θhfalse(tfalse)=hx)(t,θwith state vector x=x(t) (e.g., neutrophil concentration), parameter values θ (e.g., mean transition time), and rates of change f(x;θ,d) for given doses d.…”
Section: Methodsmentioning
confidence: 99%
“…For neutrophil‐guided dosing, a reward function was suggested that maps (MAP‐based) nadir concentrations to a continuous score 19 or penalizes the deviation from a target nadir concentration (cnormalnadir=1·109cells/L) 17 ; in this study, we used a utility function but also provide a comparison of the results with the suggested target concentration, see also Section S8.5 in Appendix and Figure . The individualized uncertainties quantified via DA allow to consider the probability of being within/outside the target range in the reward function, 21 which is more closely related to clinical reality. For the patient state of Equation used in RL, we also designed the reward function to account for efficacy and toxicity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within a Bayesian framework, typically prior knowledge about drug pharmacokinetics (PK) and exposure‐response relationships are individualized based on individual patient characteristics (“covariates,” e.g., age, weight, sex, disease characteristics, or comedication) and PK or biomarker data to obtain individual model parameters (maximum a‐ posteriori estimates). Recently, Bayesian data assimilation methods have come into focus, overcoming major limitations of maximum a posteriori ‐based approaches by enabling accurate uncertainty quantification and propagation 2 . In contrast to traditional and well‐established therapeutic drug/biomarker monitoring (TDM), MIPD provides quantitative decision support to healthcare professionals for real‐world patient populations integrating multi‐level data.…”
Section: Figurementioning
confidence: 99%